Sharia-Based Investment Strategy: Optimizing Returns and Minimizing Risks in The Capital Market - Selasi, Dini; Cucu Putria, Andieni; sutono (P3M - STAI Kuningan, 2023)
Islamic capital markets have become the focus of increasingly intense research, sparking high interest in investments that align with Islamic finance principles. This journal, entitled